NOX Emissions and Performance of a Compact Diesel Tractor Fueled with Emulsified and Non-Emulsified Biodiesel - Hunt, Chris L.; Johnson, Donald M.; Edgar, Don W. (Journal of Agricultural Systems, Technology, and Management, 2013)
A John Deere 3203 compact utility tractor (23.9 kW rated engine power) was fueled with No. 2 petroleum diesel (D2), neat biodiesel (B100), and a 10% water-in-biodiesel emulsion (Em-B100) to determine the effects on exhaust gas temperature, oxides of nitrogen (NOX) emissions, power, specific fuel consumption, and thermal efficiency under two load conditions (rated engine speed and peak torque). At rated engine speed, fueling with D2 resulted in statistically significantly (p < .05) higher exhaust gas temperatures than B100 and Em-B100; however, there were no significant differences in power take-off (PTO) specific NOX emissions. Specific fuel consumption was statistically significantly lower for D2 when compared to B100 and Em-B100, but there were no significant differences in thermal efficiency among fuels. For peak torque tests, exhaust gas temperatures were statistically significantly lower with Em-B100 than with D2 or B100. PTO specific NOX emissions with Em-B100 were equal to D2 and statistically significantly lower than B100. There was no significant difference between B100 and Em-B100 in specific fuel consumption, but specific fuel consumption for both fuels was statistically significantly higher than D2. However, fueling with B100 and Em-B100 resulted in statistically significantly higher thermal efficiencies as compared to D2. At both rated engine speed and peak torque, there were statistically significant decreases in PTO power as fuel was switched from D2 to B100 to Em-B100. These results indicate that Em-B100 has the potential to decrease NOX emissions and increase engine thermal efficiency under heavy load conditions; however, NOX reduction with Em-B100 will be at the expense of decreased power at both rated engine speed and peak torque.